Public Secondary School Students’ Perception of Vocational Education in Azerbaijan - Mirzayeva, Sara (ADA University, 2022)
This is a qualitative study that explored public lower secondary school students’ perceptions of Vocational Education and Training. Throughout the years, the government has made several efforts and implemented the state program with the aim to improve the field and attract more students to Vocational Education and Training institutions. Although those efforts succeeded to some extent, the figures show the number of students matriculating to vocational education to be significantly lower than the ones not continuing their education at any level. This study explored two research questions: (1) How do secondary school students in Azerbaijan perceive VET? (2) What are the factors influencing students’ attitudes towards and decisions about VET? To address the above-mentioned research questions, 8th and 9th -grade students from lower secondary schools were recruited. Simultaneously, the collected data were transcribed and coded to be analyzed. Document analysis and memoing were used to ensure credibility through data triangulation. The findings suggest that the participants perceive vocational education as a destination for the students with less potential. Another finding about the participants’ perception is the lack of awareness of vocational education. In addition, the findings further suggest that a number of student-related and environmental factors influence the participants’ decisions/attitudes toward vocational education. The findings of the data analysis contributed to the development of a model named Students’ Perceived Decision Model of VET. Following the discussion of the findings, implications for research and practice are presented.
Keywords: Schools, Primary.; Schools, Secondary.; Vocational Education.; Education